A UNIFIED TOOL FOR SYNCHRONIZING CHAOS IN HIGH-ORDER CHICUITS AND TIME-DELAY SYSTEMS USING A SCALAR SIGNAL - GIUSEPPE GRASSI; Saverio Mascolo (IEEE Workshop on Nonlinear Dynamics of Electronic Systems, 2000)
In this paper a novel approach for synchronizing chaotic systems with several positive Lyapunov exponents is described. The tool, which can be applied to high-order circuits as well as time-delay systems, enables synchronization to be achieved using a scalar signal.